Superior Tolerability of Altered Dosing Schedule of Sunitinib with 2-Weeks-on and 1-Week-off in Patients with Metastatic Renal Cell Carcinoma—Comparison to Standard Dosing Schedule of 4-Weeks-on and 2-Weeks-off. (27th January 2014) - Kondo, Tsunenori; Takagi, Toshio; Kobayashi, Hirohito; Iizuka, Junpei; Nozaki, Taiji; Hashimoto, Yasunobu; Ikezawa, Eri; Yoshida, Kazuhiko; Omae, Kenji; Tanabe, Kazunari
Abstract: Objective: Poor tolerability to sunitinib with the standard dosing schedule has become an issue. We retrospectively analyzed the treatment efficacy and the profile of adverse events of 2 weeks of sunitinib treatment followed by 1-week-off (Schedule 2/1) and compared the results with the standard dosing schedule with 4 weeks of treatment followed by 2-weeks-off (Schedule 4/2). Methods: From January 2010 until December 2012, 48 patients with metastatic renal cell carcinoma who received at least two cycles of sunitinib as first-line therapy were the subjects of this study. After 2011, we switched to Schedule 2/1 for most patients. Results: Schedule 2/1 included 26 patients and Schedule 4/2 had 22. The incidence of most adverse events was not significantly different between the two groups except for hand–foot syndrome and diarrhoea, which were observed more frequently in Schedule 4/2 and reached statistical significance. A dose interruption due to adverse events in the first three cycles was significantly lower in Schedule 2/1 patients than in those on Schedule 4/2 (27 versus 53% P = 0.04). With respect to treatment efficacy, the objective response rate tended to be higher in Schedule 4/2 than in Schedule 2/1 (50 versus 32%), and median progression-free survival was longer in patients on Schedule 2/1 than those on Schedule 4/2 (18.4 versus 9.1 months). These differences, however, did not reach statistical significance ( P = 0.14, P = 0.13). Conclusions: Alteration in dosing schedule of sunitinib with 2-weeks-on and 1-week-off showed a lower incidence of dose interruption and a similar oncological outcome compared with the standard dosing schedule of 4-weeks-on and 2-weeks-off.